New directions in web data management 1 - Vakali, Athena 1963-; Jain, L. C. (Studies in Computational Intelligence, 2011)
This book addresses the major issues in the Web data management related to technologies and infrastructures, methodologies and techniques as well as applications and implementations. Emphasis is placed on Web engineering and technologies, Web graph managing, searching and querying and the importance of social Web.